Job characteristics and organizational justice as antecedents of employee engagement and their consequences on turnover intention - Peñarubia, Leslie A. (Animo Repository, 2008)
The study tested a model that looked at employee engagement as a mediator between job characteristics and organizational justice and turnover intention. The study utilized a descriptive correlational design. There were 100 employees, from a single telecommunication company in the Philippines, who participated in the study. Results indicated negative correlations between employee engagement and turnover intention (r=-.276). Organizational justice and employee engagement were positively correlated (r=.314).Job characteristics and employee engagement were positively correlated(r=.205). Organizational justice and turnover intention were negatively correlated (r=.-360). Job characteristics were not related with turnover intention (r=-.101). The discussion which highlighted employee engagement was not a significant mediator in the job characteristics, organizational justice-turnover intention network (std. error=.069). The findings proposed a new model of employee engagement in which job characteristics and organizational justice mediated the relationship of employee engagement and turnover intention. The results and implications of the study were presented and discussed and series of recommendations for management level and effective Human Resources management on how to increase employee engagement and reduce turnover were made.